2013
DOI: 10.19030/tlc.v10i4.8124
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy Beliefs Of Prospective Primary Mathematics Teachers About Mathematical Literacy

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…Bu bağlamda öğretmen adaylarının ÖTMT dersini aldıktan sonra tutumlarında meydana gelen olumlu bir artışın materyal tasarlamaya yönelik öz-yeterlik inanç düzeylerini etkilediği ya da ÖTMT dersine yönelik öz-yeterlik inanç düzeylerindeki yükselmenin bu derse yönelik tutumlarını olumlu şekilde etkilediği söylenebilir. Araştırmanın bu bulguları (Arastaman, 2013;Bosswell, 2012;Conrad ve Munro, 2008;Demirel ve Akkoyunlu, 2010;Demirtaş, Cömert ve Özer, 2011;Denizoğlu, 2008;Evans, 2011;Kutluca ve Ekici, 2010;Liu, Hsieh, Cho ve Schallert, 2006;Saracaloğlu, Ünlü, Avcu ve Avcu, 2010;Saracaloğlu, Yenice ve Özden, 2013;Serin, Saracaloğlu ve Yavuz, 2010;Usta ve Korkmaz, 2010;Yavuz, Günhan, Ersoy ve Narlı, 2013) tarafından yapılan araştırma sonuçları ile paralellik göstermektedir. Son olarak öğretmen adaylarının yaratıcılık düzeyleri ile ÖTMT dersine yönelik tutum puanları arasında bir ilişki olmadığı sonucuna ulaşılmıştır.…”
Section: Tartişma Ve Sonuçunclassified
“…Bu bağlamda öğretmen adaylarının ÖTMT dersini aldıktan sonra tutumlarında meydana gelen olumlu bir artışın materyal tasarlamaya yönelik öz-yeterlik inanç düzeylerini etkilediği ya da ÖTMT dersine yönelik öz-yeterlik inanç düzeylerindeki yükselmenin bu derse yönelik tutumlarını olumlu şekilde etkilediği söylenebilir. Araştırmanın bu bulguları (Arastaman, 2013;Bosswell, 2012;Conrad ve Munro, 2008;Demirel ve Akkoyunlu, 2010;Demirtaş, Cömert ve Özer, 2011;Denizoğlu, 2008;Evans, 2011;Kutluca ve Ekici, 2010;Liu, Hsieh, Cho ve Schallert, 2006;Saracaloğlu, Ünlü, Avcu ve Avcu, 2010;Saracaloğlu, Yenice ve Özden, 2013;Serin, Saracaloğlu ve Yavuz, 2010;Usta ve Korkmaz, 2010;Yavuz, Günhan, Ersoy ve Narlı, 2013) tarafından yapılan araştırma sonuçları ile paralellik göstermektedir. Son olarak öğretmen adaylarının yaratıcılık düzeyleri ile ÖTMT dersine yönelik tutum puanları arasında bir ilişki olmadığı sonucuna ulaşılmıştır.…”
Section: Tartişma Ve Sonuçunclassified
“…Gökmen et al (2011) observed a difference in the assessment of self-efficacy among pre-service teachers by year of study, which was not confirmed in the present research study. The conclusions by Yavuz et al (2013), according to whom self-efficacy does not differ by gender, were not confirmed. By contrast, Özdemir (2008) found that women's perception of self-efficacy for classroom management was higher compared with men and suggested two possible explanations.…”
Section: Discussionmentioning
confidence: 80%
“…The studies suggest that, more often than not, practicing and prospective teachers have a positive outlook on their ability to teach mathematics to young children (Bates et al, 2011; Brown, 2005; Chen et al, 2014; Dunphy, 2009; Ertekin, 2010; Paparistodemou et al, 2014; Throndsen and Turmo, 2013; Yavuz et al, 2013), and view certain mathematical tools, such as virtual and physical manipulatives (Akkan, 2012), and computers or mobile learning devices (Doğan, 2012), to be beneficial instructional tools. As an example of the former, in a study with 346 preschool teachers, Chen et al (2013) found that 86% were confident in their ability to observe what preschoolers knew about mathematics, 84% in their ability to plan activities, and 67% in their ability to make sense of preschoolers’ confusion.…”
Section: Resultsmentioning
confidence: 99%